Angle-Selective Photonics for Smart Subambient Radiative Cooling - Liu, Fan; Zhang, Qichong (Nano-Micro Letters, 2025)
During the daytime, conventional radiative coolers disregard the directionality of thermal radiation, thereby overlooking the upward radiation from the ground. This upward radiation enhances the outward thermal radiation, leading to a substantial reduction in the subambient daytime radiative cooling performance. Conversely, radiative coolers featuring angular asymmetry and spectral selectivity effectively resolve the problem of thermal radiation directionality, successfully evading the interference caused by the ground-generated thermal radiation. This cooler overcomes the limitations posed by the angle of incident light, making it suitable for subambient daytime radiative cooling of vertical surfaces. Furthermore, by adjusting the structure of the cooler, the angular range of thermal radiation can be modulated, enabling the application of radiative cooling technology for intelligent temperature regulation of various inclined surfaces encountered in daily life. This innovative work makes a significant contribution to the development of subambient smart thermal interaction systems and opens up new possibilities for the practical application of radiative cooling technology. Highlights: 1 Subambient daytime radiative cooling of vertical surfaces is achieved by a sawtooth grating with a period significantly greater than the thermal wavelength. 2 Adjusting the grating period and aspect ratio allows the cooler to be adapted to various inclined surfaces.